THE ROLE AND SIGNIFICANCE OF LISTENING IN THE FORMATION OF COMMUNICATIVE COMPETENCE OF STUDENTS IN RUSSIAN LESSONS - Jurabekova, Khabiba (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article gives the author's opinion on the role and importance of listening in the formation of communicative competence, pays attention to the mechanisms of language learning through listening and communication in this language. The emphasis is on situations that require the attention of a student studying a foreign language in the process of listening.